Identification And Defense of Local Communities Through the Village's Original Authority - Yamin, Ahmad (Faculty of Law, Universitas Pekalongan, 2024)
Article 18B(2) of the 1945 Indonesian Constitution recognizes customary law communities and their traditional rights as long as they are alive and in accordance with the laws and regulations implemented with the birth of Law Number 6 of 2014 concerning Villages, which gives villages genuine autonomy to recognize and protect indigeous people. This research aims to 1) determine how the authority of origin recognizes and protects customary law communities and 2) how villages recognize and protect them through village rules. This study uses normative empirical methods. collect data and study documents, legal ideas and concepts, statutory regulations, legal dictionaries, and scientific works about the research issue. Data analysis in this research using main legal materials Analyze secondary laws synced with observations. This research uses qualitative analysis to explain and describe the regulations for recognizing and protecting customary law communities through village origin authority, then draws conclusions from primary and secondary legal materials. According to the research, the village can recognize and safeguard the customary law community through Village Regulations. as done by Lawin village by Village Regulation Number 1 of 2020 recognizing and protecting the Cek Bocek indigenous population. This research found that villages can recognize and protect indigenous communities through their authority of origin, which is specified in village regulations.